2010
DOI: 10.1149/1.3503519
|View full text |Cite
|
Sign up to set email alerts
|

The Oxygen Permeation Properties of Nanocrystalline CeO[sub 2] Thin Films

Abstract: The measurement of oxygen flux across nanocrystalline cerium oxide ͑CeO 2 ͒ thin films at intermediate temperature ͑650-800°C͒ is presented. Porous ceria support substrates were fabricated by sintering with carbon additions. The final dense film was deposited from an optimized sol-gel solution resulting in a mean grain size of 50 nm, which displayed oxygen flux values of up to 0.014 mol/cm 2 s over the oxygen partial pressure range from air to helium gas used in the measurement at 800°C. The oxygen flux charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nanocrystalline CeO 2 thin films were fabricated on porous cerium oxide substrates with both sol-gel and sputtering deposition techniques and studied for oxygen permeation membranes. 239 The sputtered cerium oxide buffer layer can be seen to grow in a columnar shape from the substrate-film interface (Fig. 52).…”
Section: Oxygen Permeation Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocrystalline CeO 2 thin films were fabricated on porous cerium oxide substrates with both sol-gel and sputtering deposition techniques and studied for oxygen permeation membranes. 239 The sputtered cerium oxide buffer layer can be seen to grow in a columnar shape from the substrate-film interface (Fig. 52).…”
Section: Oxygen Permeation Membranesmentioning
confidence: 99%
“…The CeO 2 thin film showed a measurable oxygen flux of 0.014 mmol cm À2 s À1 at 800 C, confirming mixed ionic and electronic conductivities and demonstrating the feasibility of utilizing nanocrystalline CeO 2 as an oxygen separation membrane with grain size as a design parameter. 239 The electronic conduction is introduced by the nanocrystalline materials structure rather than second phase additions, for example, noble metal additions commonly added in the dual phase membranes. This result is consistent with recent results reported by Haile's group using ceria nanostructuring as a route to enhance activity, rather than the traditional paradigm of metal-catalyst nanostructuring.…”
Section: Oxygen Permeation Membranesmentioning
confidence: 99%
“…(Reproduced with permission from Tuller et al [17]. Copyright 2009 by the PCCP Owner Societies), and (c) oxygen flux lmol/cm 2 s versus grain size and temperature for CeO 2 nanocrystalline membranes [19]. (Reproduced with permission from Brinkman et al [19].…”
Section: Model Single Phase Materials: Interfacial Characteristicsmentioning
confidence: 99%
“…Copyright 2009 by the PCCP Owner Societies), and (c) oxygen flux lmol/cm 2 s versus grain size and temperature for CeO 2 nanocrystalline membranes [19]. (Reproduced with permission from Brinkman et al [19]. Copyright 2010 by Journal of The Electrochemical Society.…”
Section: Model Single Phase Materials: Interfacial Characteristicsmentioning
confidence: 99%
“…They observed that samples sintered at 1400°C showed higher oxygen conductivity than those sintered at 1500°C, and argued that larger density of grain boundaries in 1400°C samples provided more area for the dopants to segregate for a given concentration of dopants. Eventually dopant segregation could cause depletion in the oxygen vacancy concentration in the vicinity of the grain boundaries as per the space-charge layer model, 101,102 thus reducing the overall conductivity. Thus, in view of these experimental observations, it appears that instead of the blocking effect of grain boundaries, larger focus may be required on preventing dopant segregation.…”
Section: Effect Of Dopant Segregation On Oxygen Energeticsmentioning
confidence: 99%